The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1088/1367-2630/ab1431
|View full text |Cite
|
Sign up to set email alerts
|

Transport signatures of a Majorana qubit and read-out-induced dephasing

Abstract: Motivated by recent proposals of Majorana qubits and the read-out of their quantum state we investigate a qubit setup formed by two parallel topological wires shunted by a superconducting bridge. The wires are further coupled to two quantum dots, which are also linked directly, thus creating an interference loop. The transport current through this system shows an interference pattern which distinguishes two basis states of the qubit in a QND measurement. We analyze various properties of the interference curren… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 39 publications
0
35
0
Order By: Relevance
“…As we are particularly interested in decoherence, i.e., the decay of off-diagonal elements of ρ(t ), this approximation is particularly well suited here. In contrast to previous works [18,19,[66][67][68][69], our approach is able to capture quantum backaction effects on the MBQ state since the quantum dynamics of the dot fermion is taken into account.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…As we are particularly interested in decoherence, i.e., the decay of off-diagonal elements of ρ(t ), this approximation is particularly well suited here. In contrast to previous works [18,19,[66][67][68][69], our approach is able to capture quantum backaction effects on the MBQ state since the quantum dynamics of the dot fermion is taken into account.…”
Section: Introductionmentioning
confidence: 96%
“…This means that (i) the readout device itself should not exchange particles with the dot-MBQ system and (ii) the decoherence due to the readout should be fast compared to decoherence caused by external noise sources which do affect the total parity. Previous theoretical studies of measurement-induced decoherence in Majorana qubits [18,19,[66][67][68][69] have analyzed related questions but without taking into account the detailed quantum dynamics of the dot and thereby, in particular, neglecting quantum backaction effects [70]. In this paper, we propose and study a flexible and powerful theoretical approach which can ultimately provide a unified and quite realistic description of the parity-to-charge conversion process and the corresponding readout dynamics in such a topologically protected system.…”
Section: Introductionmentioning
confidence: 99%
“…The most fundamental one, that of observing a quantized zero bias peak in conductance [4,11,12], can be mimicked by trivial Andreev bound states [10,[13][14][15][16] or level repulsion in multiband systems [17,18], thus several detection schemes also exploiting Majorana nonlocality have been proposed [19][20][21]. From the point of view of the applications, one of the schemes for the readout of Majorana qubits is based on transport interferometry [22,23], providing further motivation to explore the transport properties of Majorana devices.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, these studies neglect thermal excitations while focussing on dephasing and relaxation in a minimal model of four Majorana zero-modes. Decoherence of Majorana zero-modes in presence of a bath, in particular in the context of Majorana qubits, has been studied using a similar theoretical framework as the present work based on a quantum master equation [41][42][43][44]. These studies have demonstrated the general susceptibility of Majorana zero-modes to environment-induced potential fluctuations in finite systems.…”
Section: Introductionmentioning
confidence: 86%